The Role Of Economic Digitalization From An Islamic Perspective - Wulandari, Henik; Firnanda, Shinta Nuriya (INAIFAS Press, 2025)
The development of technology in the economic field has impacted individual mobility, where individuals seek quick solutions, with everything just a tap away to purchase their needs or desires. Through internet connectivity, they can access media platforms provided by sellers in the e-commerce industry. The aim of this study is to understand the role of economic digitalization from an Islamic perspective. The method used is a literature study. Various sources are analyzed to draw conclusions from this research. Technological development in this field is also aligned with Islamic principles or Shariah to ensure consumer trust when purchasing products offered by sellers. The result of this study is that technological development in the economic sector does not ignore Islamic principles as guidelines, commonly known as Shariah, which ensures that consumers or buyers are not harmed, avoiding any harm and is based on values of truth in the economic system.